Peranan Kompensasi Dalam Meningkatkan Kesejahteraan Dan Kinerja Karyawan Pada Roti Bakar Hj. Ade - Hilwa Syafira Barkah; Uus MD Fadli (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This research was conducted with the aim of knowing the effect of the compensation given to Roti Bakar HJ UMKM. Ade so that he can improve the performance of employees and wants to know how the form of compensation for the UMKM Roti Bakar HJ is. Ade and the role of compensation on employee performance. This study uses a qualitative method. The research was conducted at Perum Delta Jati Kota Block B3. No 5 RT/RW 005/013 Adiarsa Timur, East Karawang, Karawang, West Java. The data source used is the primary data source through interviews with previously determined informants. Data collection techniques used are interviews, observation, and documentation. The results showed that the owner of Roti Bakar Hj. Ade's company consistently strives to meet the needs of its employees so it is clear that with the help of the tools provided by him, these employees are motivated to work harder and achieve greater success. The conclusion of this study is that the compensation provided by the company will make employees motivated to continue to develop so that their performance within the company also increases and develops.